Performance analysis of porous solar absorbers with high-temperature radiation cooling function - Yu, Haiyan; Chen, Anqi; Li, Mingdong; Hailati, Ahali; Wu, Xiaohu; Ren, Xiaohan (Chinese physics B, 2025)
In order to meet the growing global energy demand and fulfill energy conservation and emission reduction goals, the efficient utilization of solar energy is becoming increasingly critical. However, the effects of high temperatures on solar absorption are rarely considered in practical research. Therefore, this study presents a porous zinc and silver sulfide solar absorber with high-temperature radiative cooling capabilities. The solar absorption rate and radiative cooling efficiency in the high-temperature range (636 K–1060 K) are computed using the finite-difference time-domain method. Furthermore, the impact of parameters such as characteristic length, porosity, incident angle, and pore shape factor on both the absorption rate and efficiency of the solar absorber is analyzed. The mechanism is further examined from the perspective of microscopic thermal radiation. The results show that, in the high-temperature range, the solar absorption rate increases with higher porosity and incident angles, reaching its peak when the characteristic length is 1 μm. These findings highlight the significant potential of the solar absorber for efficient solar energy harvesting in photo-thermal conversion applications within a specific high-temperature range.